Cultivating human beings, not human doings: challenging discourses of self care - J. Nicole Little (Scottish Journal of Residential Child Care)
To what do we owe the project of human doings over human beings? Self-care has long been sanctioned as the root of Child and Youth Care (CYC) practitioner resilience. This argument is faulty in its individualistic and "doing" ways. Instead, the author proposes that we need to connect with vulnerability and love as a means to accomplish self and other-care. Critiquing contemporary discourses of self-care, the author draws on Buddhist philosophy and Radically Open Dialectical Behaviour Therapy (RO-DBT) as a means to deconstruct this.